Termofisiolofia da vespa Polybia (Trichothorax) ignobilis (Haliday, 1836) (Hymenoptera, Vespidae, Epiponini) durante a atividade de forrageamento - Tsuyama, Paula [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Many social wasps are known to use thermogenesis to warm up their flight muscles and are therefore able to forage under a broad range of ambient temperatures. However it is uncertain whether there exists a possible relation between ambient temperature and thermogenic capacity for tropical species, as we lack studies focusing on these species. Therefore, we examined the use of this mechanism in the neotropical Epiponini wasp Polybia ignobilis. More specifically, we used a thermographic camera to obtain data of the surface temperatures of three body regions (head, thorax and abdomen) of wasps during foraging activities (pre-flight, flight and post-flight) in cold [initial pe- riod of foraging activity: TAM : 15 − 20◦C] and warm [final period of foraging activity: TPM : 30 − 35◦C] conditions. Thorax temperature (Tth) was always higher than head (Th) and abdomen temperature (Tabd). In general, the lowest body temperatures were observed during the pre-flight period, while the highest values occurred upon the return of the wasps from the foraging flight. Except for the pre-flight period, Tth was always higher than Tabd, indicating that heat generated at the thorax was preferentially directed to the cephalic region. Therefore we confirmed the use of thermogenesis by a neotropical social wasp, although its magnitude was found modest compared to temperate species, which suggests a link between thermal environment and thermogenic capacity. We also showed that P. ignobilis modulates heat production as a function of ambient temperature (TA), maintaining a greater temperature difference (Tbody − TA) at cooler temperatures. Finally, we identified the cephalic region of wasps as an important route for the dissipation of the heat generated during flight

Muitas vespas sociais são conhecidas por usar a termogênese para aquecer seus músculos de voo permitindo forragear sob uma ampla gama de temperaturas ambientes. No entanto, é incerto se existe uma possível relação entre a temperatura ambiente e a capacidade termogênica para espécies tropicais, como nos falta estudos que incidem sobre estas espécies. No presente trabalho, foi analisada a termogênese em vespas neotropicais Polybia ignobilis. Os dados foram obtidos com auxílio de uma câmera termográfica, onde analisou-se a temperatura superficial de diferentes regiões do corpo (cabeça, tórax e abdômen) das vespas durante atividades de forrageamento (pré-voo, voo, e pós-voo) em condições quentes e frias (Tºam: 15-20 ºC e Tºpm: 30-35 ºC), tendo como objetivo a obtenção de informações a respeito da influência da atividade de forrageamento na temperatura corporal. Com a análise dos dados obtidos confirmou-se o uso de termogênese por uma vespa social, neotropical, embora sua magnitude seja modesta em comparação com espécies de clima temperado, o que sugere uma ligação entre o ambiente térmico e capacidade termogênica. Também se concluiu que P. ignobilis modula a produção de calor em função da temperatura ambiente (Tºa), mantendo uma maior diferença de temperatura (Tºbody - Tºa) em temperaturas mais baixas. Além disso, identificouse a região cefálica de vespas como uma via importante para a dissipação do calor gerado durante o voo
Keywords: Vespa; Termografia; Animais - Alimentos; Fisiologia veterinaria; Temperatura corporal - Regulação